Bibliometrics in a Digital Age: Help or Hindrance. (September 2018) - Blakeman, Karen
Bibliometrics are a range of techniques and quantitative measures that provide an analysis of written publications such as books and articles, and which assess the impact of research outputs. They are commonly applied to individual authors in the form of citation metrics but can also be used to assess the influence of research groups or even entire institutions. With the increased importance of social media as a means of communicating and publicising research findings, additional alternative measures of impact (altmetrics) are now being used. In addition to analysing the reach of a research output, bibliometrics can also be used as search tools to identify related and updated research, author networks and connections between institutions. This review summarises the range of tools and services that are available, their advantages and disadvantages, and some of the challenges and issues presented by the existence of multiple digital versions of research outputs.